EXPLORING BANDARBAN THROUGH TREKKING TRAILS: A NEW HORIZON FOR COMMUNITY-BASED TOURISM DEVELOPMENT - Hasan, Syed Rashidul; Islam, Md. Saiful (European Scientific Journal, ESJ, 2015)
Bandarban is regarded as one of the most attractive travel destinations in Bangladesh. This is the most potential tourist destination that will certainly flourish in near future. But no significant attempts have been made to explore and exploit this potential sector in Bandarban. Consequently, the benefit of tourism has remained very limited for the local people. The purpose of the study was to identify and explore different trekking routes of Bandarban for adventure-loving tourists. Further, another objective was to identify possible further involvement of the local communities in tourism through which they can upgrade their economic status. Community-based tourism development can be the most suitable concept not only for community development but for tourism development in Bandarban also. In this study, some potential trekking trails have been identified as well as discovering some potential ways of involving local ethnic communities living alongside the trekking trails in tourism.